2022
DOI: 10.1038/s41467-022-32681-7
|View full text |Cite
|
Sign up to set email alerts
|

Divergent changes in particulate and mineral-associated organic carbon upon permafrost thaw

Abstract: Permafrost thaw can stimulate microbial decomposition and induce soil carbon (C) loss, potentially triggering a positive C-climate feedback. However, earlier observations have concentrated on bulk soil C dynamics upon permafrost thaw, with limited evidence involving soil C fractions. Here, we explore how the functionally distinct fractions, including particulate and mineral-associated organic C (POC and MAOC) as well as iron-bound organic C (OC-Fe), respond to permafrost thaw using systematic measurements deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 82 publications
0
26
0
1
Order By: Relevance
“…Studies have pointed out that water-stable aggregates with a diameter greater than 0.250 mm contain more particulate organic C (POC), lighter-group organic C (LFOC), and higher microbial biomass C (MBC). This indicates that the large aggregates have low organic C stability [68][69][70]. Based on the study of loess soil, it is also shown that the oxidizable organic C in loess soils mainly concentrates in the 0.2-2 mm large aggregates particle group, while the stable aromatic organic C concentrates in the particle groups smaller than 0.002 mm [71].…”
Section: Soil Physical C Sequestrationmentioning
confidence: 99%
“…Studies have pointed out that water-stable aggregates with a diameter greater than 0.250 mm contain more particulate organic C (POC), lighter-group organic C (LFOC), and higher microbial biomass C (MBC). This indicates that the large aggregates have low organic C stability [68][69][70]. Based on the study of loess soil, it is also shown that the oxidizable organic C in loess soils mainly concentrates in the 0.2-2 mm large aggregates particle group, while the stable aromatic organic C concentrates in the particle groups smaller than 0.002 mm [71].…”
Section: Soil Physical C Sequestrationmentioning
confidence: 99%
“…In the permafrost region of the TP, the cold environment sequesters a large amount of soil organic carbon (Ding et al, 2016). The degradation of permafrost caused by rising ground temperature accelerates the exposure, decomposition and lateral transport of this organic carbon to rivers, which leads to the acceleration of greenhouse gas emissions possibly enhancing climate warming in a positive feedback effect (Liu et al, 2022;Zhang et al, 2020b). Further, the sustained increase in ground temperature in the glacier areas of the TP will accelerate glacier melting and collapse, which will promote lake expansion and increase runoff in the basin in the short term.…”
Section: Implications Of Persistent Increases In Ground Temperaturementioning
confidence: 99%
“…Natural clay particles have hydrophilic properties, a high capacity for adsorption, and a specific surface area and are harmless to humans. , In soil environments, the deposition process of DOM is mainly adsorption on the surface of soil minerals, which have many physical and chemical reaction sites for organic groups, especially clay-sized particles. Spatially complex and active environs within the soil minerals’ porous structure support the high adsorption of DOM. , Based on these, it may be feasible to explore a soil-inspired material designed and synthesized using a bottom-up approach for DOM removal. In fact, adsorption to the surfaces of CaP and clay minerals and precipitation as secondary CaP minerals are predominant reactions for DOM in soil due to the surface complexation ligand exchange reactions .…”
Section: Introductionmentioning
confidence: 99%